2023
DOI: 10.1007/s00210-023-02678-0
|View full text |Cite
|
Sign up to set email alerts
|

Echinochrome exhibits anti-asthmatic activity through the suppression of airway inflammation, oxidative stress, and histopathological alterations in ovalbumin-induced asthma in BALB/c mice

Islam Ahmed Abdelmawgood,
Noha A. Mahana,
Abeer Mahmoud Badr
et al.

Abstract: Asthma is a chronic pulmonary disease with marked infiltrating inflammatory cells and reduced respiratory performance. Echinochrome (Ech) is a dark-red pigment isolated from the sea urchin spines, shells, and ova. It has antioxidant, antimicrobial, and anti-inflammatory properties, but whether it can be used in asthma treatment has yet to be investigated. In this research, we aimed to study the inhibitory actions of Ech on allergic asthma symptoms in mice. Mice were divided into 4 groups (n = 8 for each): cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
1
0
0
Order By: Relevance
“…We found that LY294002 significantly reduced nasal scratching scores of OVA-LPS-challenged mice. Moreover, neutrophil numbers and IL-17 levels in BALF were significantly increased in these challenged mice compared to that in control mice, suggesting that the neutrophilic airway inflammation mouse model was established as previously reported [ 19 , 20 ]. These results were further confirmed neutrophil numbers in sputum, BALF and bronchial biopsies were higher in neutrophilic asthma than those of control mice.…”
Section: Discussionsupporting
confidence: 72%
“…We found that LY294002 significantly reduced nasal scratching scores of OVA-LPS-challenged mice. Moreover, neutrophil numbers and IL-17 levels in BALF were significantly increased in these challenged mice compared to that in control mice, suggesting that the neutrophilic airway inflammation mouse model was established as previously reported [ 19 , 20 ]. These results were further confirmed neutrophil numbers in sputum, BALF and bronchial biopsies were higher in neutrophilic asthma than those of control mice.…”
Section: Discussionsupporting
confidence: 72%